Design of functionally graded materials by selective laser melting - Nair, Adarsh Ravikumaran (Nanyang Technological University, 2021)
Additive manufacturing has the unique capability of forming materials point by point and layer by layer with spatially varying microstructures. By engineering the microstructure, it is possible to build components with enhanced properties known as Functionally Graded Materials (FGM). FGM can be fabricated in various ways such as mesostructures optimization, alloy composition gradient, nano twinning, or microstructure control. A process parameter study was conducted on selective laser melted 316L to print highly textured blocks (up to 23 times random distribution) with >99% density. The ability to spatially control texture is then demonstrated by printing checkerboard patterns of alternating controlled texture. It was found that additional considerations such as laser penetration depth must be accounted for to print samples with multiple discrete textures. Finally, finite element simulations are included to demonstrate potential applications for controlling deformation in components with site-specific materials properties.